DESENVOLVIMENTO DE UM APLICATIVO HIPERMÍDIA COM O USO DO FEEDBACK PROCESSUAL COMO RECURSO DIDÁTICO VOLTADO AO ENSINO DE ELETRICIDADE NO ENSINO MÉDIO - Gastaldo, Luis Fernando (2009)
This master's dissertation in the area of concentration in the teaching of physics developed in the professional master's degree in Mestrado Profissionalizante em Ensino de Física e Matemática do Centro Universitário Franciscano of the Santa Maria, describes the development of an educational hypermedia application addressing the concept of electrical resistance in the teaching of physics in high schools. This hypermedia application developed in Flash enabled progress in the use of the feedback process, a feedback of character education, which aims to allow the monitoring of the navigation of your users so that the teacher can delineate the relationships developed by students in the construction of its knowledge and intervene when necessary, making learning more meaningful to the student. The methodology used in the organization pedagogical of hypermedia educational is based on three pedagogical moments which are initial problematization, organization of knowledge and application of knowledge. The theoretical foundation adopted was the theory of meaningful learning of Ausubel. It is reported in this work, the implementation of this application in a hypermedia experience teaching in two classrooms of a public school in high school. This experiment presents some results obtained from questionnaires and reports submitted by students. We present an analysis of each screen used in the hypermedia application developed and relate some testimonials from students who show some of his notions about the operation of electrical equipment such as showers and lamps. After examination of the hypermedia application and use of feedback process as a tool for navigation, consider the positive contributions derived from this product developed. This alternative pedagogical showed itself capable of keeping up the integrated teaching of physical prompting students to realize and understand that about your physical experience reality.